RELIABILITY OF BITE MARK ANALYSIS AS A TOOL FOR FORENSIC INVESTIGATION (Journal of Forensic Medicine & Toxicology, 2022)
Aim: 1. To determine the Feasibility of bite mark analysis in forensic investigation 2. To evaluate the Reliability of bite mark analysis 3. To evaluate the Acceptability of bite mark as evidence Materials and Methods: Photographs of Bite Marks of 50 consenting volunteers were taken. Impressions of Bite  The findings showed that among the three methods  The bite mark analysis has to be used for as This is followed by Computer Assisted Hand Tracing Overlay Technique which is Reliable but has to be used cautiously due to inter-observer bias. The Metric method has proved to be Unreliable, hence has to be avoided.
Keywords: Bite mark; Photography; Metric measurement; Computer assisted Bite mark analysis; dentition scan method; Inter-observer variations